Microtremor Survey Method: A New Approach for Geothermal Exploration - Baoqing, Tian; Zhifeng, Ding; Liming, Yang; Yifan, Fan; Bo, Zhang (Frontiers in Earth Science, 2022)
Geothermal resources are a type of sustainable and green energy, which can play an important role in emission peaks and carbon neutrality. Determining the best development target area is key to resource development and geophysical methods are commonly used for this purpose. Owing to serious human and industrial interference, the microtremor survey method is often adopted for geothermal exploration in urban areas. It is a passive source method, which is non-invasive and environmentally friendly. In this method, the Rayleigh wave dispersion curve is extracted using spatial autocorrelation based on the vertical component signal at the observation station. A genetic algorithm is used to invert the dispersion curve of one survey point to obtain strata parameters such as layer thickness, S-wave velocity, and density. It provides critical parameters for the cap layer and reservoirs for geothermal exploration. For a chain microtremor measurement, a two-dimensional (2D) apparent S-wave velocity section can be generated. The apparent S-wave velocity is calculated from the phase velocity using the following empirical method: the 2D apparent S-wave velocity section helps to identify the buried channel for heat flow and track the irregular shapes of the reservoirs or cap layers. It has been verified that the microtremor survey method is reliable and accurate compared with borehole materials. As a newly developed non-invasive geophysical method, it can be widely used in geothermal exploration.